HUMAN IMMUNODEFICIENCY VIRUS AND ACQUIREDIMMUNE DEFICIENCY SYNDROME AS HUMAN GLOBAL SECURITY CHALLENGE IN THE 21 ST CENTURY - Elijah Onyango Standslause, Odhiambo; William Oluoch, Ligawa,; Kassilly, Dr.Janet (IJRDO - Journal of Social Science and Humanities Research, 2016)
In this article, we explore the human security ramifications of the global AIDS pandemic. We illustrate how HIV/AIDS is a threat to the human insecurity of millions of people because ofthe lethal nature of the illness and the widespread lack of access to anti-retroviral drugs in the developing world. The article show that the AIDS pandemic also poses a profound indirect threat to human security because of the wider social consequences the pandemic is having in the most affected regions. HIV/AIDS is therefore not just one human security issue amongst many, but constitutes one of the most urgent human security challenges in the twenty-first century. The article concludes by outlining the implications of the HIV/AIDS pandemic for debates about the utility of the ‘human security’ concept.